Effect of honokiol on the induction of drug-metabolizing enzymes in human hepatocytes - Cho YY; Jeong HU; Kim JH; Lee HS (Dove Medical Press, 2014)
Yong-Yeon Cho,1 Hyeon-Uk Jeong,1 Jeong-Han Kim,2 Hye Suk Lee1 1College of Pharmacy, The Catholic University of Korea, Bucheon, Korea; 2Department of Agricultural Biotechnology, Seoul National University, Seoul, Korea Abstract: Honokiol, 2-(4-hydroxy-3-prop-2-enyl-phenyl)-4-prop-2-enyl-phenol, an active component of Magnolia officinalis and Magnolia grandiflora, exerts various pharmacological activities such as antitumorigenic, antioxidative, anti-inflammatory, neurotrophic, and antithrombotic effects. To investigate whether honokiol acts as a perpetrator in drug interactions, messenger ribonucleic acid (mRNA) levels of phase I and II drug-metabolizing enzymes, including cytochrome P450 (CYP), UDP-glucuronosyltransferase (UGT), and sulfotransferase 2A1 (SULT2A1), were analyzed by real-time reverse transcription polymerase chain reaction following 48-hour honokiol exposure in three independent cryopreserved human hepatocyte cultures. Honokiol treatment at the highest concentration tested (50 µM) increased the CYP2B6 mRNA level and CYP2B6-catalyzed bupropion hydroxylase activity more than two-fold in three different hepatocyte cultures, indicating that honokiol induces CYP2B6 at higher concentrations. However, honokiol treatment (0.5–50 µM) did not significantly alter the mRNA levels of phase I enzymes (CYP1A2, CYP3A4, CYP2C8, CYP2C9, and CYP2C19) or phase II enzymes (UGT1A1, UGT1A4, UGT1A9, UGT2B7, and SULT2A1) in cryopreserved human hepatocyte cultures. CYP1A2-catalyzed phenacetin O-deethylase and CYP3A4-catalyzed midazolam 1'-hydroxylase activities were not affected by 48-hour honokiol treatment in cryopreserved human hepatocytes. These results indicate that honokiol is a weak CYP2B6 inducer and is unlikely to increase the metabolism of concomitant CYP2B6 substrates and cause pharmacokinetic-based drug interactions in humans. Keywords: honokiol, human hepatocytes, drug interactions, cytochrome P450, UDP-glucuronosyltransferases